Strategies For Citation And Reference Management In Scientific Writing - Muhammad Reza Tengkhu Rafi Pasya (JPNM Jurnal Pustaka Nusantara Multidisiplin, 2026)
Errors in citation and referencing practices in students’ academic writing remain common and pose a threat to academic integrity while increasing the risk of plagiarism. Therefore, a proper understanding of citation techniques and the use of credible sources is essential in scientific writing. This study aims to explain the definition, functions, types, and procedures of writing citations and references in accordance with scientific standards. In addition, the study seeks to identify the academic consequences resulting from improper citation practices. This research employs a descriptive-analytical approach through a literature review of various scholarly sources discussing citation and referencing practices, common problems encountered by students, and relevant cases of academic misconduct. The results indicate that the most frequent errors include improper citation formatting, the use of non-credible sources, and inconsistencies between in-text citations and the reference list. These errors can reduce the quality of academic work, weaken research validity, and potentially lead to academic sanctions or even legal consequences. Therefore, higher education institutions need to strengthen training programs, technical guidelines, and information literacy to improve authors’ accuracy, prevent plagiarism, and maintain credibility and trust in the academic community.